Does Entrepreneurial Culture Influence Students’ Entrepreneurial Intention? - Mohamad Syaefudin, Neli Purwani, Agus Wibowo (International Journal of Advanced Science and Technology, 2020)
Entrepreneurship culture and education have become a pivotal aspect of the formation of a student’s entrepreneurial intentions. This study examines the influence of entrepreneurial culture, entrepreneurship education, and mindset on entrepreneurial intentions. This study used a quantitative research method using a survey model. The participants of this study were recruited from 253 respondents studying languages at public universities in Indonesia. The results show that four hypotheses were accepted. First, entrepreneurial culture influences students’entrepreneurial education. Second, entrepreneurial culture influences students’ entrepreneurial mindset. Third, entrepreneurial education influences students’ entrepreneurial intentions. Fourth, the entrepreneurial mindset mediates the effect of entrepreneurial education on students’ entrepreneurial intentions. Keywords: Entrepreneurial Education, Entrepreneurial Intention, Entrepreneurial mindset, Students of language department